Tourists' mindsets and choice of adventurous holiday activities. Issue 15 (3rd August 2021) - Japutra, Arnold; Hossain, Muhammad Ismail
ABSTRACT: People's mindsets are considered vital since mindsets influence their behaviours. Surprisingly, research investigating how mindsets influence tourists' behaviours is very scarce. The present study examines the effects of tourists' mindsets on the choice of holiday activities in a scenario-based experiment. In a 2 × 2 study, which includes tourist mindsets (fixed, growth) and the perception of adventurousness (high, low) of the holiday activities, we show that mindsets influence the choice of holiday activities. Tourists who endorsed growth mindset tend to choose more adventurous activities, while tourists who endorsed fixed mindset seem to be indifferent. The implications for these findings for destination managers are discussed.